Bioactivity‐guided isolation of anti‐inflammatory limonins from Chukrasia tabularis. Issue 12 (9th August 2022) - Shen, Jin‐Huang; Zhang, Yi‐Fan; Zhang, Li; Yang, Na‐Na; Ma, Xin‐Hua; Zhong, Tian‐Hua; Zhang, Yong‐Hong
Abstract: Chukrasia tabularis is an economically important tree and widely cultured in the southeast of China. Its barks, leaves, and fruits are consumed as a traditional medicine and perceived as a valuable source for bioactive limonin compounds. The extracts from root barks of C. tabularis showed significant anti‐inflammatory effect. The aim of this research was to explore the material basis of C. tabularis anti‐inflammatory activity, and to purify and identify anti‐inflammatory active ingredients. By a bioassay‐guided isolation of dichloromethane fraction obtained two novel phragmalin limonins, Chukrasitin D and E (1 and 2 ), together with 12 known limonins (3 –14 ). The chemical structure of these compounds is determined on the basis of extensive spectral analysis and chemical reactivity. In addition, the activities of these isolated limonins on the production of nitric oxide (NO), tumor necrosis factor alpha (TNF‐α), and nuclear factor kappa B (NF‐ κ B) in RAW264.7 cells induced by lipopolysaccharide (LPS) were evaluated. Limonins 1 and 2 indicated significant anti‐inflammatory activity with IC50 values of 6.24 and 6.13  μ M. Compound 1 notably inhibited the production of NF‐ κ B, TNF‐ α and interleukin 6 (IL‐6) in macrophages . The present results suggest that the root barks of C. tabularis exhibited anti‐inflammatory effect and the limonins may be responsible for this activity. Abstract : Isolating limonins from Chukrasia tabularis including two new limonins and twelve known limonins. The limonins showed significant anti‐inflammatory activity in LPS‐induced RAW 264.7 cells. Compound 1 notably inhibited the production of NF‐κB, TNF‐α and IL‐6 in macrophages.